2004
DOI: 10.1177/0363546503258864
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Knee Temperature Changes

Abstract: Both methods produced large declines in skin and IA temperatures. However, ice was more effective yet resulted in higher pain scores. The authors hypothesize that IA temperatures below a threshold are associated with increased perceived pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 18 publications
2
53
1
4
Order By: Relevance
“…The temperature measurement of the knee joint has a long history in medical thermometry (Ammer, 2012;Ho et al, 1994;Sanchez-Inchausti et al, 2005). However most of the measurements are based-skin (Becher et al, 2008;Oosterveld and Rasker, 1994) or are intra-articular (Martin et al, 2001;Warren et al, 2004), which cannot discriminate between heat generated by dissipation and heat generated by muscles and transported via the vascular system. Nevertheless, some studies have reported the increase of temperature subsequent to mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature measurement of the knee joint has a long history in medical thermometry (Ammer, 2012;Ho et al, 1994;Sanchez-Inchausti et al, 2005). However most of the measurements are based-skin (Becher et al, 2008;Oosterveld and Rasker, 1994) or are intra-articular (Martin et al, 2001;Warren et al, 2004), which cannot discriminate between heat generated by dissipation and heat generated by muscles and transported via the vascular system. Nevertheless, some studies have reported the increase of temperature subsequent to mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…107,124 We also utilize various therapeutic lasers to aid in the healing response. 31,58,118 Treatment options for swelling include cryotherapy, 15,32,125,135,169 high-voltage stimulation, 74 and joint compression through the use of a knee sleeve or compression wrap. 91 A commercial cold device (FIGURE 2) providing continuous cold therapy and compression may also be beneficial.…”
Section: Restore Patellar Mobilitymentioning
confidence: 99%
“…Several studies have analyzed the efficacy of cryotherapy modalities for reducing cutaneous [8][9][10][11][12][13][14] , intramuscular 7,9,[14][15][16] and articular 17 temperature. Previous studies have identified that a crushed ice pack, ice massage and cold water immersion are the most effective modalities for inducing greater and faster cooling [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%